Internalization of Sincere Character Education and Devotion of Students Through Ngabula at the Al-Mubarok Miftahul Ulum Bindeng Sampang Islamic Boarding School - Latifa Julianti; Luthfatul Qibtiyah (Penerbit Hellow Pustaka, 2026)
This study examines the process of internalizing the values ​​of sincere character and the attitude of reverence of students through ngabula activities at the Al-Mubarok Miftahul Ulum Bindeng Sampang Islamic Boarding School. The background of this study is the importance of character education in forming a generation that has faith, sincerity, and respect for teachers, as well as the ability to face moral challenges in society. The problems raised in this study are 1. how is the internalization of sincere character education and the attitude of reverence of students through ngabula at the Al-Mubarok Miftahul Ulum Bindeng Sampang Islamic Boarding School 2. What are the supporting and inhibiting factors in internalizing the character education of sincere and the attitude of reverence of students through ngabula at the Al-Mubarok Miftahul Ulum Bindeng Sampang Islamic Boarding School. This study uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with kyai, nyai, and kabula students. Data analysis in this study uses the Saldana, Miles, and Huberman models. The data analysis process is through data condensation, data presentation and verification of conclusions. The results of the study show that the internalization of the values ​​of sincerity and the attitude of reverence of students is carried out through three stages: namely transformation through book studies, transactions through giving advice and motivation, and transinternalization through habituation or special guidance. The supporting factors in the internalization of the values ​​of the character of sincerity and the attitude of reverence through ngabula activities include the culture of the Islamic boarding school that upholds religious values ​​and an environment that supports character formation and also special guidance from caregivers and support from the parents of the kabula students. While the inhibiting factors include the lack of understanding of the kabula students about the values ​​during the ngabula period, namely the importance of the values ​​of sincerity and the attitude of reverence in ngabula, as well as the influence of the environment outside the Islamic boarding school and also from the kabula students themselves, namely sometimes being lazy in carrying out tasks and delays in personal tasks of the kabula students due to the large number of ngabula tasks.